EFEKTIVITAS PROGRAM PELATIHAN DALAM UPTD BALAI LATIHAN KERJA DINAS TENAGA KERJA TRANSMIGRASI DAN SOSIAL KABUPATEN BLORA - Candra, Muhammad Adhif Alfi; Sulandari, Susi (Journal of Public Policy and Management Review, 2017)
Training Center is a government agencies that is implementing vocational training programs, trial training program, competency test and empowerment training institution in the field of industry. The training that held is Competency Based Training by opening some areas of competencies that required in the field of industry. The effectiveness of the training program is on resources allocation activity are appropriately targeted and programmed by the government as a public servant as a form of investment that is in the form of skilled labor, competitive labor and competent labor by upgrading their capability programmatically through training agencies or Hall. The indicator to rate effectiveness of training program according to Gomes (2003), which is based on the reaction, learning progress, behavior change, results, and cost effectiveness. This research is done by descriptive analysis method with quantitative approach. To analyse the data is using frequency distribution with mean, median, and mode and also including a chart. The conclusion of this research, level of the effectiveness of training programs in UPTD Training Center Department of Manpower, Transmigration and Social of Blora regency overall based on the analysis and data processing has been quite effective. However, there some aspects that are considered low and need improvement in the level of satisfaction will be training on aspects of participants reaction. To improve the effectiveness of the training program, its necessary to improve the quality of service at the center, and the placement of labor due to the amount of placement of labor after training is still low, and then the cooperation with the stakeholders is still limited.